Cell Structure Improvement in Melt Processed Pure Aluminium Foams by Pre-treatment of Foaming Mixture. Issue 1 (1st July 2022) - Gandhapu, Sandeep; Mahajan, Aryan; Sasikumar, S
Abstract: This work aims to evaluate the cell structure of aluminium foams blown by using foaming mixture subjected under ball milling and heat treatments. This paper presents the study on the effects of various pre-treatment of foaming mixture on the cell structure of foamed aluminium (Al) fabricated via melt route. This study also demonstrates how the melt foaming method can be used to fabricate small-sized Al foams. Prior to foaming the Al melt, the foaming mixture containing TiH2 and Al was pre-treated by ball milling and heat treatment in four different ways. The foaming mixtures were characterized by X-ray diffraction (XRD), Energy Dispersive X-ray Analysis (EDAX) and Scanning Electron Microscope (SEM) techniques. The macrostructure of the foams has been characterized by optical scanner and ImageJ software. The mechanical properties of the foam samples were evaluated by quasi-static compression test. XRD results revealed the TiO2 and Ti3 O phases formed in the heat treated TiH2 powders. SEM micrographs showed the morphological changes occurred to Al and TiH2 powders and their distribution before and after ball milling. EDAX reported the chemical composition of elements present in the foaming mixtures. Ball milled foaming mixture not only increases the number of TiH2 particles, but also reduces the hydrogen content during the foaming stage. The foam produced from heat-treated and ball-milled foaming mixture shows better cell size & structure with good homogeneity. However, the mechanically mixed foaming mixture produce foam with good strength and energy absorption capability.